Neonatal, infant, and under-5 mortality and morbidity burden in the Eastern Mediterranean region: findings from the Global Burden of Disease 2015 study - Khalil, Ibrahim; Jonas, Jost B.; Mokdad, Ali (International journal of public health, 2018)
OBJECTIVES: Although substantial reductions in under-5 mortality have been observed during the past 35 years, progress in the Eastern Mediterranean Region (EMR) has been uneven. This paper provides an overview of child mortality and morbidity in the EMR based on the Global Burden of Disease (GBD) study. - METHODS: We used GBD 2015 study results to explore under-5 mortality and morbidity in EMR countries. - RESULTS: In 2015, 755,844 (95% uncertainty interval (UI) 712,064-801,565) children under 5 died in the EMR. In the early neonatal category, deaths in the EMR decreased by 22.4%, compared to 42.4% globally. The rate of years of life lost per 100,000 population under 5 decreased 54.38% from 177,537 (173,812-181,463) in 1990 to 80,985 (76,308-85,876) in 2015; the rate of years lived with disability decreased by 0.57% in the EMR compared to 9.97% globally. - CONCLUSIONS: Our findings call for accelerated action to decrease child morbidity and mortality in the EMR. Governments and organizations should coordinate efforts to address this burden. Political commitment is needed to ensure that child health receives the resources needed to end preventable deaths.
Published online: 3 August 2017
Gesehen am 14.05.2020
GBD 2015 Eastern Mediterranean Region Adolescent Health Collaborators: I. Khalil, J.B. Jonas, A.H. Mokdad [und 164 weitere]